Keterampilan bermain bola voli pada peserta seleksi pekan olahraga pelajar daerah - Salsabila, Putri Hawa; Achmad, Irfan Zinat; Gani, Ruslan Abdul (Universitas Hamzanwadi, 2023)
The purpose of this study was to determine the skills of playing volleyball in the selection participants of the regional student sports week (POPDA). Descriptive quantitative research approach. This research method is a survey with a volleyball playing skills test. The population of all POPDA selection participants amounted to 172 people. The sample was taken with simple random sampling technique, totaling 120 people consisting of setter 30, libero 16, middle block 34, opposite 16, and outside hitter 34. The results of the study of volleyball playing skills of POPDA selection participants were in the